PENGARUH MANAJEMEN LABA DAN TAX PLANNING TERHADAP PAJAK PENGHASILAN BADAN TERUTANG PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2022 - Kumala, Ratih; Bongnathan, Michelle Brigita (Jurnal Ilmu Administrasi Publik, 2025)
The purpose of this study is to determine the extent of the influence of earnings management and tax planning on corporate income tax payable. The population used in this study is the Manufacturing Companies in the Miscellaneous Industrial Sector listed on the Indonesia Stock Exchange (IDX) in 2020-2022. The research method used is descriptive quantitative, with the sample determined using purposive sampling, resulting in a sample of 8 companies based on predetermined criteria with the assistance of Eviews software version 12. A total of 24 data points will be tested using descriptive statistical tests, classical assumption tests, and hypothesis testing. The results of this study indicate that earnings management does not affect corporate income tax payable, tax planning does not affect corporate income tax payable, and collectively, earnings management and tax planning do not affect corporate income tax payable.